Christian Accommodative Mindfulness: Definition, Current Research, and Group Protocol - Garzon, Fernando (Religions, 2022)
More clinicians are using mindfulness-based therapeutic strategies; however, Evangelical Christian clients sometimes worry about the Buddhist origins of these treatments. Christian accommodative mindfulness (CAM) attempts to address these concerns with culturally sensitive adaptations to mindfulness methods. We present a definition of CAM and propose some worldview adjustments to typical mindfulness constructs when working with these clients. The empirical research on Christian-derived meditation strategies and Christian-adapted mindfulness strategies will then be reviewed. We introduce a four-session group CAM protocol currently being researched that focuses on scripture meditation, breath meditation, body awareness, and loving-kindness meditation. Sample scripts are included.